(untitled) (Research, Society and Development, 2023)
In the Amazon, the natural conditions of low fertility and high soil acidity pose major challenges for maintaining agricultural production. Under these circumstances, organic matter is essential for soil quality, influencing its physical, chemical and biological attributes. The constant supply of biomass in a forest promotes nutrient cycling, making available, in part, the nutrients needed for plant development. The same does not occur in the agricultural areas, where the removal of vegetation cover and the lack of proper management considerably affect the sustainability of the production systems. The objective of this work was, therefore, to highlight the importance of the organic matter for the conservation of soils in the Amazon, discussing the impacts of deforestation on soil quality and relevant aspects for its recovery. In order to do that, scientific articles indexed in online databases published in the last fifteen years were consulted, as well as books, dissertations, theses and technical publications. The implementation of agroforestry systems stands out as an option for the recovery of degraded areas in the Amazon, although there are several challenges for its use, such as the lack of information about which species to use in each situation. The recovery of degraded soils requires specific projects that take into account, among other aspects, the use of key species to ensure the success of this process, requiring studies to assess the performance of species best adapted to the different climate and soil conditions of the areas to be recovered.